380 TREATMENT OF ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY (TENTACLE—ESOPHAGUS) STUDY: OUTCOME OF VARIOUS LEAKAGE TREATMENTS. (14th September 2020) - Van Workum, F; Verstegen, M; Ubels, S; Hannink, G; Klarenbeek, B; Rosman, C; Bouwense, S
Abstract:  : Anastomotic leakage (AL) is a common and severe complication after esophagectomy. It is largely unknown which initial treatments are most effective for what type of leak. We aimed to investigate the effectiveness of initial treatments of AL in daily clinical practice. Methods: The TENTACLE—Esophagus is a multinational retrospective cohort study, in which patients with AL after esophagectomy with gastric tube reconstruction in the period 2011–2019 were included. Detailed data regarding casemix, surgery, leak characteristics (e.g. organ failure, leak circumference, contamination, drains present) and treatment (e.g. hours from diagnosis to treatment, treatment modalities) were collected. Primary outcome was 90-day mortality and secondary outcomes included length of stay and leak healing time. Regression analysis will be used to analyze the effectiveness of primary treatments after correction for patient-, surgery- and leak characteristics. The full study protocol is accessible at www.tentaclestudy.com . Results: Detailed data of 1407 patients with AL from 70 centers in 20 countries is currently being validated and is awaiting final analysis. Preliminary results showed that AL was diagnosed 0–43 days after surgery and 90-day mortality rate was 11.1%. Primary treatments included re-operation (23.0%), stenting (16.8%), radiological drainage (10.5%), tube placement through the defect in the leak cavity (8.7%) and endoVAC placement (3.4%). Re-operations (n = 323) were drainage only (54.6%), oversewing the leak (15.5%), anastomotic resection and re-anastomosis (5, 3%), repair with muscle flap (2.5%), disconnection and esophagostomy (11.8%) and other or unknown procedures (10.3%). Conclusion: This is the largest study on effectiveness of AL treatments. The final results of initial leak treatments, which will be available for presentation at the ISDE meeting, could provide an evidence based basis that can be used by clinicians to determine the preferred primary treatment strategy in patients with a given type of AL.